MENEMUKAN KEMBALI TUJUAN PEMASARAN MELALUI STRATEGIC THINKING DI ERA TEKNOPOLI - Aditya Nirwana; Melany (Universitas Sarjanawiyata Tamansiswa, 2023)
The provision of digital marketing training to SMEs (Small and Medium-sized Enterprises) perceived as technologically lagging often simplifies the complexity of marketing. The focus on technology operation sometimes neglects crucial aspects of more substantial marketing. Through literature review, this paper attempts to explore the situation related to the reduction of marketing complexity by technology in the context of the phenomenon and strives to synthesize an idea within the framework of strategic marketing as a way out of the current issues. SMEs, as businesses, face various complex issues that require in-depth understanding, such as financial management, production, human resources, strategic planning, quality assurance, and marketing. However, the solutions offered are often reductive, treating technology as an instant solution. This occurs due to a lack of planning and evaluation in digital marketing. The academic community's community engagement teams sometimes overlook the needs of SMEs and impose technocratic training, merely to fulfill academic obligations. This phenomenon is referred to as a technopoly culture, where technology is perceived as an authority without considering real issues. A reorientation of goals is needed through strategic thinking in digital marketing training to avoid reductionism. This paper proposes the concept of Strategic Thinking to help identify needs, adapt approaches, measure success, and involve relevant stakeholders to create a significant impact on SMEs' development in the digital era.